A new videokymography system for evaluation of the vibration pattern of entire vocal folds. Issue 3 (June 2016) - Wang, Soo-Geun; Park, Hee-June; Lee, Byung-Joo; Lee, Sung-Mo; Ko, Bumjun; Lee, Sang Min; Park, Young Min
Abstract: Objective: To overcome the limitations of previous videokymography methods, we developed a new videokymography system for the evaluation of the whole mucosal wave of the entire vocal cord mucous membrane. Methods: To confirm the usefulness of the new videokymography system, we performed videokymography to evaluate the mucosal wave of the vocal folds during modal and falsetto phonation in normal adult males. Additionally, we serially performed both laryngeal videostroboscopy and the new videokymography method in patients diagnosed with acute ulcerative laryngitis. Results: Using the new videokymography system, the mucosal wave pattern of entire vocal folds was captured during the examination. The opening and closing durations could be differentiated, and the symmetry of amplitude and phase could be assessed. The shape of the medial and lateral peaks could be assessed. In patients with acute laryngitis, the new videokymography system showed an enhanced ability to evaluate the flexibility of the vocal folds. Conclusion: The new videokymography system enables recording of the whole mucosal wave pattern of entire vocal folds. Although further studies are required to confirm its clinical efficacy for the evaluation of vocal folds, the system can be applied to evaluate the static and dynamic status of vocal folds in patients with vocal cord diseases.